OPTIMIZATION OF COLLABORATIVE GOVERNANCE-BASED VILLAGE POTENTIAL. - Adji Suradji Muhammad; Kurniawan Prasetyanta (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to find out how collaborative governance is implemented to optimize village potential. Collaborative governance is a form of cooperation between government, private, and community parties. The methodology used in this research is a qualitative one. The qualitative method is a research method that aims to explore and understand social phenomena. This method is believed to be in accordance with the existing phenomenon of the availability of local potential that exists but has not been managed and utilized optimally to bring about people's welfare. Based on the data and findings during the research, it can be seen that the local potentials in the form of Koro swords and Aloe vera have been managed and utilized by the village community. The involvement of higher education in empowering the community to utilize the potential of the village is believed to be able to provide optimal benefits.